2001
DOI: 10.1303/aez.2001.489
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of germinated broad bean seeds as an oviposition substrate in mass rearing of the predatory bug, Orius sauteri (Poppius) (Heteroptera: Anthocoridae).

Abstract: Utilization of germinated broad bean seed (Vicia faba L.) as an alternative oviposition substrate for Orius sauteri (Poppius), a candidate biological control agent against thrips, was investigated under condition of 24°C and 16L : 8D. O. sauteri could lay eggs in a juvenile root of germinated broad bean seed provided as an oviposition substrate and these eggs could hatch with 97.1% hatch rate. Both nymphs and adults of O. sauteri were successfully reared on diet of the Mediterranean flour moth eggs (Ephestia k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
2
9
0
3
Order By: Relevance
“…Richards & Schmidt (1996) relataram que as fêmeas de O. insidiosus selecionaram para a oviposição locais protegidos e que não estão sujeitos a rápida dessecação. Também, Murai et al (2001) insidiosus foi mantido com brotos de feijão ou brotos de soja (4,3 ± 0,28 e 3,9 ± 0,21 ovos por dia, respectivamente), comparado aos demais substratos (P<0,05), resultando em um número total de ovos igual a 63,9 ± 1,66 e 59,7 ± 1,12 ovos, respectivamente (Tabela I). Este fato pode estar relacionado com a relativa maciez e turgidez destes brotos, o que facilitou a oviposição, pois o teor de umidade pode ser um importante fator de estímulo para oviposição de O. insidiosus.…”
Section: Resultsunclassified
See 2 more Smart Citations
“…Richards & Schmidt (1996) relataram que as fêmeas de O. insidiosus selecionaram para a oviposição locais protegidos e que não estão sujeitos a rápida dessecação. Também, Murai et al (2001) insidiosus foi mantido com brotos de feijão ou brotos de soja (4,3 ± 0,28 e 3,9 ± 0,21 ovos por dia, respectivamente), comparado aos demais substratos (P<0,05), resultando em um número total de ovos igual a 63,9 ± 1,66 e 59,7 ± 1,12 ovos, respectivamente (Tabela I). Este fato pode estar relacionado com a relativa maciez e turgidez destes brotos, o que facilitou a oviposição, pois o teor de umidade pode ser um importante fator de estímulo para oviposição de O. insidiosus.…”
Section: Resultsunclassified
“…Wang et al (1999) utilizaram brotos de feijão como substrato de oviposição e de fonte de água para adultos e ninfas de Orius strigicollis (Poppius, 1909) e relataram que as ninfas apresentaram um melhor desenvolvimento e sobrevivência sobre esse substrato, comparado com ninfas criadas sobre vagem de feijão ou folhas de berinjela. Murai et al (2001) verificaram uma viabilidade de ovo a adulto de 90,3% para O. sauteri mantidos em brotos de feijão.…”
Section: Fig 1 Número Acumulado De Ovos Produzidos Por Recipiente Dunclassified
See 1 more Smart Citation
“…kuehniella eggs, commonly used to rear anthocorid species (Arijs and De Clercq, 2001;Bueno et al, 2006;Fauvel et al, 1994;Murai et al, 2001;SamsoePetersen et al, 1989;Yanik and Unlu, 2011;Yanik and Unlu, 2015), were used to rear A. minki. Since anthocorid bugs lay their eggs in the tissue of plants, faba beans have been commonly used as the oviposition substrate for Orius spp., the anthocorid predators (Castañé and Zalom, 1994;Linus et al, 2002;Murai et al, 2001;Ruberson et al, 1991;Richards and Schmidt, 1996;Venzon et al, 2002). Faba beans that can be obtained throughout the year, an advantage for mass rearing (Murai et al, 2001), were also successfully used as the oviposition substrate for A. minki.…”
Section: Discussionmentioning
confidence: 99%
“…Since anthocorid bugs lay their eggs in the tissue of plants, faba beans have been commonly used as the oviposition substrate for Orius spp., the anthocorid predators (Castañé and Zalom, 1994;Linus et al, 2002;Murai et al, 2001;Ruberson et al, 1991;Richards and Schmidt, 1996;Venzon et al, 2002). Faba beans that can be obtained throughout the year, an advantage for mass rearing (Murai et al, 2001), were also successfully used as the oviposition substrate for A. minki. Anderson (1962) reported that A. minki prefers psyllids as prey.…”
Section: Discussionmentioning
confidence: 99%